Ultra-broadband absorber from visible to near-infrared using plasmonic metamaterial - Lei, Lei; Li, Shun; Huang, Haixuan; Tao, Keyu; Xu, Ping (Optics express, 2018)
We propose a design of an ultra-broadband absorber based on a thin metamaterial nanostructure composed of a periodic array of titanium-silica (Ti-SiO ) cubes and an aluminum (Al) bottom film. The proposed structure can achieve nearly perfect absorption with an average absorbance of 97% spanning a broad range from visible to near-infrared (i.e., from 354 nm to 1066 nm), showing a 90% absorption bandwidth over 712 nm, and the peak absorption is up to 99.8%. The excitation of superior surface plasmon resonance combined with the resonance induced by the metal-insulator-metal Fabry-Perot (FP) cavity leads to this broadband perfect absorption. The polarization and angle insensitivity is demonstrated by analyzing the absorption performance with oblique incidences for both TE- and TM-polarized waves. In addition, we discuss the impact of various metal materials and geometry structure on absorption performance in detail. The proposed broadband metamaterial absorber shows a promising prospect in applications such as solar cell, infrared detection, and imaging. Moreover, the use of a thin titanium cap and an aluminum film instead of noble metals has the potential to reduce production cost in applications.